Including soil organic carbon into nationally determined contributions: Insights from Ghana - Diwediga, Badabat; Chabi, Adeyemi; Arinloye, Djalal A.; Chesterman, Sabrina; Vågen, Tor-Gunnar; Aynekulu, Ermias; Winowiecki, Leigh Ann (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Healthy soils are the foundation of sustainable and regenerative food systems and provide several vital ecosystem services. Sequestering carbon in agricultural soils, for example, can have mutual benefits for climate change mitigation and adaptation, food and nutrition security, biodiversity, and water resilience. Despite these benefits, there are few policies that incentivize farmers to invest in maintaining and improving soil health. This policy brief highlights opportunities for the inclusion of soil health and soil organic carbon (SOC) into the National Determined Contributions (NDC) as a key step for governments to support farmers to invest in their soil. This activity builds on recent assessments including a paper that extensively reviewed the first-round of 184 NDCs concluding that only 28 countries referred to SOC, peatlands or wetlands (Weise et al., 2021). This review and the subsequent interviews with experts (n=8) indicated the importance of understanding the impact of land management on SOC storage and dynamics (Weise et al., 2021). As a follow-up, Rose et al (202) focused on the updated NDCs and found that the number of countries that included SOC in their updated NDC increased compared to the first-round NDC process (Rose et al., 2021). This review also highlighted that 19 countries highlighted the need for financing for SOC and related measures (Rose et al., 2021).